Influences of borrowing on pricing decisions of market vendors in the Tacloban supermarket - Lacaba, Harold B. (Danyag : Journal of Humanities and Social Sciences, 2007)
Market vendors' inability to access capital from formal lending or financial institutions usually makes them captive to predatory lending schemes. With the high interest rates charged by the said lending schemes coupled by their inability to prepare and interpret their financial status and results of operations, these market vendors may not have an idea of where their businesses are going. This paper seeks to determine the borrowing and the costs of borrowing of market vendors and how these costs affect their pricing decisions. This study used the Du Pont model for the computation of the rate of return to assess the viabillity of the market vendors' current operation. The computed average rate of return was then compared to the average cost of borrowing of market vendors. To assess the relationship between the cost of borrowing and the pricing decisions of market vendors, the researcher used the Pearson Correlation Coefficient (r). Using Guilford's suggested interpretation for correlation coefficient values, this study found out that at 5% and 10% interest rates, there is a low negative correlation between the amount borrowed and mark-up rate while there is a moderate negative correlation at 15% and 20% interest rates. Further, this research evaluates the financial status and results of operations of market vendors through financial ratio analysis to determine how market vendors should price their commodities to be more profitable and sustainable.